Current status of endoscopic ultrasound for the upper gastrointestinal tract in Asia - Yoshinaga, S.; Hilmi, I.N.; Kwek, B.E.A.; Hara, K.; Goda, K. (Wiley, 2015)
We summarize the current status of endoscopic ultrasound (EUS) for the upper gastrointestinal (GI) tract solely in Asia, focusing on the staging of superficial cancers and the diagnosis of submucosal tumors (SMT), by analysis of questionnaire responses and a literature review. EUS for assessing the depth of superficial cancers of the upper GI tract is useful; however, evidence is lacking to support that EUS is superior to other modalities. The current status of EUS varies across different Asian countries, and standardization of the methods used both during the procedure and for depth subclassification is necessary to evaluate the diagnostic accuracy. Although EUS alone is limited in the diagnosis of SMT, EUS-guided fine-needle aspiration is an effective and safe diagnostic tool. Although there is a role for EUS, there are still many limitations both technically and in terms of accessibility.